Analisis Struktur Mekanik Pada Mesin 3D Printer (CNC Hybrid 3-Axis) Menggunakan Software Autodesk Inventor 2018 - Anju Pritia Dapa; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The automation machine technology has been widely developed to help overcome the problems in manufacturing performance. One of the developed machines were the 3D Printer machine that can be used in various professional work fields. One of the machines developed by Riau University students is a 3D Printer machine called the CNC Hybrid 3-Axis Machine. However, there has been no research to examine whether this machine is safe to operate. Thus, the author took the initiative to determine the quality of the mechanical structure on the machine frame. Structural analysis studies and determines the effects of loads on physical structures and their components. The method used for the research on the mechanical structure of this machine is through manual calculation analysis and finite element method analysis using the Autodesk Inventor 2018 application. Each analysis is carried out on every part of the machine that experiences movement in the direction of the X-Axis, Y-Axis and Z-Axis parts, the frame and the machine legs. Through the results of the analysis, it can be seen that the maximum stress that occurs in the X-axis slider frame is 30.687 MPa from manual calculations and 29.81 MPa from the Autodesk Inventor simulation. The maximum deflection value occurs in the engine frame and the largest maximum deflection value occurs at the slider of X-Axis with a value of 0,3543 mm. By comparing the results of manual structural analysis and finite element analysis simulations, it can be seen that the structural frame has a safety factor value above 15 so it is safe to use and operate in the future. Keywords: CNC Hybrid 3-Axis, Structure Analysis, X-Axis, Y-Axis, Z-Axis.